KPU Strategy South Tangerang City in Increasing Voter Participation During Pandemic Times at The Election in 2020 - Endang Sulastri; Lusi Andriyani; Achmad Mudjahid Zein (Research Synergy Foundation, 2023)
Voter participation in an election is often a measure of election success. The higher the level of participation, the higher the public's trust in the election process and the stronger the legitimacy of the elected leader. The City of South Tangerang, which has participated in the regional elections three times until the last election in 2020, has had an interesting experience regarding voter participation. In the previous regional elections, namely in 2010 and 2015, voter participation was never more than 60%. In the 2010 elections, voter participation only reached 56.9%, and in the 2015 elections even decreased to only 56.8%. This number is very far from the average target for regional election participation. In 2020 elections were held during a pandemic, and there was concern that voter participation would decline further. In fact, voter participation rose to 60.48%. From the initial survey, it was found that the KPU of South Tangerang City before the election was worried that participation would decline, so they developed a strategy to increase voter participation. This study aims to determine the strategy for increasing voter participation carried out by the KPU of South Tangerang City in the 2020 elections and to find out the challenges, obstacles, and supporting strengths. The theory used in this study is the theory of voter participation from Hungtinfton, Verba, and Kaats, as well as findings in journals related to strategies for increasing participation. The research method uses a qualitative approach with a descriptive method. Data collection techniques through interviews and documentation. Data analysis: qualitative based on Miles and Huberman. Test the Validity of the Data using Triangulation. The result research showed that the KPU of South Tangerang City, in an effort to increase the level of political participation, used a strategy with the P Process model by starting to use vision and mission analysis, identifying problems, formulating strategies by making activities plans, implementing strategies through socialization with five types of activities: competitions, virtual meetings, print journalism, social media and distribution of visual aids for socialization purposes. All implementations are monitored and evaluated both in the middle and at the end of the activities.